UJI TOKSISITAS MERKURI (Hg) TERHADAP ORGAN GINJAL PADA TIKUS GALUR WISTAR (Rattus norvegicus) DENGAN PEMERIKSAAN UREUM DAN KREATININ SERTA HISTOPATOLOGI GINJAL - Narindro - Karsanto; Dian Kresnadipayana; Yemima Adelia Narang (LPPM Universitas Abdurrab, 2024)
Heavy metals have a bad effect for the body of animals and humans. The heavy metal that has the highest toxicity is mercury. Mercury (Hydrargyrum) is a chemical compound that is toxic to the body. Exposure to mercury that enters the body can cause acute and chronic poisoning effects as well as disturbances in various organ systems of the body. This study aims to determine the effect of subchronic toxicity on the kidneys by examining levels of urea, creatinine and histopathology of rat’s kidney organs. In this preclinical study, the toxic compound used was mercury sulfate in powder form, then dissolved in aquabidest. This study used 12 male rats divided into 4 groups. The first group, the control group was given aquabidest solution, the 3 treatment groups were given mercury sulfate preparations at a dose of 10 mg/Kg BW, 20 mg/Kg BW, 30 mg/Kg BW. This research lasted for 4 weeks. Urea levels were checked three times, namely at week 0, week 2, and week 4 during the treatment period. At the end of the examination, the test animals were sacrificed for histopathological examination. Administration of mercury sulfate with varying doses had an effect on the kidneys of rats as seen from the results of examination of unstable urea and creatinine levels, namely decreased and increased from normal limits, as well as histopathological examination of the kidneys which showed damage to the parts of the kidney. The conclusion of this study was that there was a toxic effect on the kidneys of white rats when exposed to mercury sulfate orally with graded doses for 4 weeks.